Racial differences in sleep duration intersect with sex, socioeconomic status, and U.S. geographic region: The REGARDS study - Petrov, Megan E. (Sleep Health, 2020)
OBJECTIVES: Short and long sleep duration are associated with poor health outcomes and are most prevalent among racial/ethnic minorities. Few studies have investigated the intersection of other sociodemographic characteristics with race/ethnicity on sleep duration prevalence. DESIGN: Longitudinal retrospective analysis of continental U.S. cohort, the REasons for Geographic And Racial Differences in Stroke (REGARDS) PARTICIPANTS: Black (n = 7,547) and white (n = 12,341) adults, 56% women, ≥45 years MEASUREMENTS: At baseline (2003–07), participants reported age, sex, race, education, income, marital status, U.S. region, and employment status. The weighted average of reported sleep duration on weekdays and weekends, assessed at follow-up (2008–10), was categorized as <6, 6.0–6.99, 7.0–7.99 [reference], 8.0–8.99, and ≥9 h. Multinomial logistic regression models examined the independent and multivariable associations of sociodemographic factors with sleep duration. Interactions terms between race with education, income, region, and sex were examined. RESULTS: Average sleep duration was 7.0 h (SD=1.3). Prevalence of short (<6 h) and long(≥9 h) sleep duration was 11.4% (n = 2,260) and 7.0% (n = 1,395), respectively. In the multivariable model, interactions terms race*income, race*sex, and race*region were significant (P < .05). Relative to white adults, black adults, were most likely to have short sleep duration. The magnitude of that likelihood increased across greater levels of household income, but with greatest odds among black adults living outside of the Southeast and Appalachian United States, particularly for men (≥$75k; black men OR = 5.47, 95%CI: 3.94, 7.54; black women OR = 4.28, 95%CI: 3.08, 5.96). CONCLUSIONS: Race in the context of socioeconomic, sex, and regional factors should be examined as key modifiers of sleep duration.